ENVIRONMENTAL FRIENDLY FIELD TOURISM MANAGEMENT FROM THE PERCEPTION AND EMPOWERMENT OF FARMERS AND LAND OWNERS IN PUNGGUR KECIL VILLAGE, KUBU RAYA REGENCY - Irsan, Robby; Soeryamssoeka, SB.; Fitrianingsih, Yulisa (Jurnal Teknik Sipil, 2022)
Prospects in tourism especially rice field tourism are being encouraged so that rural communities become independent both financial and sectoral. The concept of a tourism village is a form of community based tourism (CBT). The concept used in CBT is closely related to empowerment. Based on the identification and analysis of the problem, the solution that can be given is to develop community-based and sustainable tourism, to avoid uncontrolled land conversion, to raise public awareness by implementing environmental-based economic management and to harmonize the understanding of land owners to farming communities in ecotourism land management sustainable fields. The problems identified from the results of the FGD are the level of knowledge, attitudes, motivation, and experience of farmers towards the establishment of ecotourism in rice fields. This research was conducted using the PRA (Participatory Rural Appraisal) approach. Several techniques for implementing PRA include: (a) historical path tracing, (b) development needs tracing, (c) livelihood analysis, (d) preparation of activity plans, (e) focus group discussion, (f) mapping. The outputs from this research are (1) roadmap for developing Punggur Kecil agro-tourism village. (2) capacity building of knowledge, attitude, motivation, and experience of farmers in the development of ecotourism in paddy fields. The stages of implementing this research are planning, coordination with village government and land owners, group discussion forums, making a rice field ecotourism road map, mentoring, and monitoring and evaluation.